Müntz Spectral Method for Two-Dimensional Space-Fractional Convection-Diffusion Equation (Communications in Computational Physics, 2019)
In this paper, we propose and analyze a Müntz spectral method for a classof two-dimensional space-fractional convection-diffusion equations. The proposedmethods make new use of the fractional polynomials, also known as Müntz polynomials, which can be regarded as continuation of our previous work. The extension istwofold. Firstly, the existing Müntz spectral method for fractional differential equationwith fractional derivative order 0
Keywords: Two-dimension space-fractional convection-diffusion equation; singularity; Müntz polynomials; Müntz spectral method; Crank-Nicolson scheme; spectral accuracy.